Evaluating the Heterogeneous Effect of Firm Risk on Firm Value - Nhung Nguyen, Thi Hong (SEISENSE Journal of Management, 2020)
Purpose- This paper aims to investigate the effect of firm risk on the firm value to see how the firm value is changing when the risk level is changed. Our result indicates that a higher level of risk can reduce firm value.  Design/Methodology- We apply a Bayesian causal technique for a sample data set of US public firms. The causal approach helps us to focus on the reliable and unbiased results instead of the association-based findings. Findings- The results show a negative effect of risk on the firms’ value for the sample data. However, we investigate the potential effect of the risk across the distribution of the firm value. We witness the more substantial effect of risk on firms with a higher value. Practical Implications- Helps firms to evaluate their risk and its effect, so they can adjust their decisions and take actions to reduce the undesired effects of firm risk.